Feasibility Analysis of Kubota Four-Wheel Tractor Service Service Business Model L3608 And Model L4018 In Tanah Miring District, Merauke District - Jerry Fernanda; Ineke Nursih Widyantari; Riza Fachrizal (Journal of Global Sustainable Agriculture, 2024)
This research aims to 1) Analyze the income of Kubota's four-wheeled tractor service business Model L3608 and Model L4018. 2) Analyzing whether the four-wheeled tractor Kubota Model L3608 and Model L4018 service business is feasible. The research is conducted in Tanah Miring District, Merauke Regency. The population in this study consisted of 30 business owners of four-wheeled tractor service Kubota Model L3608 and Model L4018, and the census method was used for sample selection. The data analysis used is cost, revenue, depreciation, income, and RC ratio feasibility analysis. The results of the study obtained the income of Kubota four-wheeled tractor service business Model L3608 and Model L4018 in Tanah Miring District, Merauke Regency, which amounted to Rp 9,617,827.40 for four-wheeled tractor Model L3608, and Rp 14,331,283.40 for four-wheeled tractor Model L4018. The feasibility analysis of the Kubota Model L3608 and Model L4018 four-wheeled tractor service business in Tanah Miring District, Merauke Regency, is feasible, with an RC ratio of 1.26 for the Model L3608 four-wheeled tractor, and an RC ratio of 1.45 for the Model L4018 four-wheeled tractor.